The DEVELOPING THE SPEAKING SKILLS OF THE STUDENTS THROUGH DRAMA TECHNIQUE - Djafar, Suriani; Syukri; Muhammad Yunus (Universitas Terbuka, 2023)
One of the techniques that can be used to improve students’ ability in speaking is by performing a drama in English class. Therefore, drama provides more chances for the students to speak and in English fluently and accurately. Moreover, the students are motivated to speak and express their feeling. The objective of the research was to examine whether or not the use of drama technique can improve the speaking skills of the eleventh-grade students of SMA Negeri 6 Gowa. The research used a pre-experimental method with 35 eleventh-grade students as respondents. Data of the research was collected by using the speaking test. The result showed that using drama technique can develop students speaking skills. It is seen from the significant level; 0,005<0.05. students’ scores. The mean score of the pre-test is 48,32, and the post-test is 68,18. It means that the use of drama techniques can improve the students’ speaking skills significantly. The showed concluded that using drama technique in teaching speaking skills can develop the students’ speaking skills. Keywords: Teaching Speaking, drama, developing students’ speaking